Radon and progeny (Pb-214 and Bi-214) in urban water-supply systems of São Paulo State, Brazil - Bonotto, Daniel Marcos [UNESP]; Padron-Armada, Priscilla Cardoso [UNESP] (Pergamon-Elsevier B.V. Ltd, 2008)
Many water-supply systems in South America utilize the waters of the Guarani aquifer at least as part of their networks. However, there is little present knowledge in Brazil of the factors affecting Rn presence in the water supplied for end-users, despite the economic importance of Guarani aquifer. Rn-222 analyzes of 162 water samples were performed at 8 municipalities in São Paulo State, Brazil, with the aim of investigating the major factors affecting its presence in solution. The Rn-222 activity concentration ranged from 0.04 up to 204.9 Bq/L, with three samples exceeding the World Health Organization maximum limit of 100Bq/L. Aeration was confirmed as the most important factor for Rn release, as expected due to its gaseous nature. Accumulation in pipes and stratification in the water column were other significant factors explaining the data obtained in some circumstances. The Rn daughters Ph-214 and Bi-214 were also determined in a set of selected samples and their presence was directly related to the occurrence of Rn dissolved in water. (c) 2008 Elsevier Ltd. All rights reserved.